Mathematical Communication Skills in Terms of Student Learning Motivation on ARCS Model with Immediate Feedback - Iva Lutviana; Kartono Kartono; Isnarto Isnarto (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
This research objective is to describe mathematical communicarion skill through ARCS- IF Model based on learners motivation. Type of this research is Mixed Method with concurrent embedded designs. This research population was Eight grader of SMP Maarif Kyai Gading Demak 2020/ 2021. Result of this research showed that ARCS- IF learning is effective in learners mathematical communication skill. Result of learners description with high learners motivation categories were able to complete mathematical communication skill with the indicator ability to express mathematical idea to write and convey them visually. Ability in stating idea or situation of problem into mathematical models (pictures, graphs, diagrams, tables and equations), ability to use right formulas in solving problems, students with motivation categories students are being able to complete communication skills mathematical with indicators Motivation learners were Ability to express mathematical ideas in writing and express them visually, Ability to use right formula to solve problems, students with low motivation categories were able to complete mathematical communication skills with Low Motivation indicators Ability to express mathematical idea to write and convey them visually.